Carga imediata em implantes unitários: revisão da literatura - Jassé, Fernanda Ferreira [UNESP]; Segalla, José Cláudio Martins [UNESP]; Silva, Marcos Aurélio Bonfim da [UNESP]; Porto, Rosângela de Oliveira; Calistrato, Raquel Saldanha [UNESP]; Saad, José Roberto Cury [UNESP] (My University, 2010)
The possibilities of treatment with dental implants have revolutionized the field of oral rehabilitation in recent years, bringing a number of advantages over conventional prostheses. For years, a surgical protocol was followed that called for maintaining the implant without load for a certain period for osseointegration, but experimental studies have shown that immediate loading of implants also leads to the formation of peri-implant bone tissue along the time, similarly to that observed for conventionally loaded implants. This study aimed to conduct a literature review regarding the use of this alternative rehabilitation with single implants. The immediate loading of single-tooth replacements is presented as an excellent treatment alternative.

As possibilidades de tratamento com implantes odontológicos revolucionaram a área de reabilitação bucal nos últimos anos, trazendo uma série de vantagens sobre as próteses convencionais. Durante anos, foi seguido um protocolo cirúrgico que preconizava a manutenção do implante sem carga por um determinado período para que ocorresse a osseointegração. Porém, estudos experimentais têm mostrado que a carga imediata em implantes também promove formação de tecido ósseo peri-implantar ao longo do tempo, de maneira comparável àquele observado para implantes com carga convencional. Assim, este estudo teve como objetivo realizar revisão da literatura quanto ao uso dessa alternativa de reabilitação com implantes unitários. A técnica de carga imediata em implantes unitários se apresentou como uma excelente alternativa de tratamento.
Immediate loading of single-tooth implants: literature review
Keywords: Dental implant; Immediate load; Implant-supported dental prosthesis; Implante dentário; Carga imediata; Prótese dentária fixada por implante